Prevalence of smoking in a rural community of Bangladesh - Akhtar, Shaheen; Numan, Sharker Md.; Ahmed, Sohel; Anwar, Mustafa (International Journal Of Community Medicine And Public Health, 2017)
Background:Smoking is a global public health concern. It causes huge premature death, health issues and possess economic burden in the developing countries. Despite of mass anti-smoking camping prevalence of smoking is increasing in developing countries. The aim of this study was to determine the prevalence of smoking and factors associated with smoking among a rural population of Bangladesh. Methods:A cross-sectional study was designed to collect data from rural community of Bangladesh in February to April 2011. Sample was determined purposively and size was 500. Results:The study’s current smoking prevalence was 39.4%. Respondents mean age was 34.63 years and current smokers mean age was 35.7SD ± 9.23 years. The prevalence of current smoking amongst male (89.3%) was significantly higher in comparison with the female (10.7%). Current smoking habit had been gradually decreased with the level of education. The prevalence of current smoking was significantly (P = 0.000) highest among the day labour (30.5%) and two-third smokers was initiated to smoking within the age of 10 to 20 years. About 36.4% of the current smokers smoked 5 to 15 sticks per day. Both ever (42%) and current (45.2%) smoking prevalence was highest amongst the population those monthly family income below 5000 Taka (60 USD). Conclusions:Overall rural smoking prevalence was 39.4%. Ever and current smoking prevalence was significantly higher among males. Smoking prevalence was highest among the illiterate and reduced with the increase of level of education and socio-economic status. To reduce the smoking prevalence amongst the risk group, policy-maker should be implementing massive anti-smoking program.